A novel layer-structured PtN₂: first-principles calculations - Fan, C.Z.; Li, J.; Hu, M.; Zhao, Z.S.; Xu, B.; He, J.L. (Сверхтвердые материалы, 2013)
Platinum nitride as the first successfully synthesized noble metal nitride shows superior mechanical properties and exotic electronic structure that rival those of conventional transition metal nitrides. In the past diverse crystal structures have been proposed to understand its unusual properties. However, very few works pay attention to the dynamic stability of these phases. Here, we examine the potential structures of platinum nitride with a chemical composition of PtN₂ by utilizing a widely adopted evolutionary methodology for crystal structure prediction. Except reproducing the previously proposed phases, we also identify a Pmmm symmetric novel layer structure with a low formation enthalpy that is slightly lower than those of marcasite and CoSb₂ structures but slightly higher than that of pyrite structure. The elastic constants and the lattice dynamical calculations show that this layer-structured PtN₂ is mechanically and dynamically stable. The calculated band structures suggest this new phase together with the simple tetragonal phase are metallic, while other phases are insulators. In addition, it is found that the fluorite structure is dynamically unstable by the phonon spectrum calculations, although it is mechanically stable as suggested by calculated elastic constants.